2015
DOI: 10.1080/15384047.2015.1121345
|View full text |Cite|
|
Sign up to set email alerts
|

Upregulation of PP2Ac predicts poor prognosis and contributes to aggressiveness in hepatocellular carcinoma

Abstract: Protein phosphatase 2A (PP2A) is a heterotrimeric protein phosphatase consisting of a 36-k D catalytic C subunit (PP2Ac). This study aimed to explore the prognostic and biological significance of PP2Ac in human hepatocellular carcinoma (HCC). High PP2Ac expression was significantly (P < 0.01) associated with serum hepatitis B surface antigen positivity, serum hepatitis B e antigen positivity, liver cirrhosis, moderate to poor differentiation grade, advanced disease stage, intrahepatic metastasis, and early rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 37 publications
(40 reference statements)
1
14
0
Order By: Relevance
“…Several selective inhibitors (e.g., C646) for histone acetyltransferase like CBP and P300 have been used to study the inhibitory effect on HBV transcription (Tropberger et al, 2015). The prodrug GS-5801 has also been shown to inhibit transcription from cccDNA by blocking the activity of lysine demethylase 5 (KDM5) (Gilmore et al, 2017). Although these observations show that silencing of HBV transcription is possible, the main throwback of most of these targets is the lack of desired selectivity for cccDNA and their potential to impact cellular processes.…”
Section: Modalities Acting On Cccdnamentioning
confidence: 99%
“…Several selective inhibitors (e.g., C646) for histone acetyltransferase like CBP and P300 have been used to study the inhibitory effect on HBV transcription (Tropberger et al, 2015). The prodrug GS-5801 has also been shown to inhibit transcription from cccDNA by blocking the activity of lysine demethylase 5 (KDM5) (Gilmore et al, 2017). Although these observations show that silencing of HBV transcription is possible, the main throwback of most of these targets is the lack of desired selectivity for cccDNA and their potential to impact cellular processes.…”
Section: Modalities Acting On Cccdnamentioning
confidence: 99%
“…These issues need to be further explored. However, the involvement of MC-LR and ctHBx in carcinogenesis and progression is not wellunderstood, particularly with respect to regulation of PP2A enzyme activity to activate downstream MAPK signaling in hepatocellular carcinogenesis (Gong et al, 2015;Cheng et al, 2018), which is associated with changes in cell proliferation and invasion and in the cell cycle. This study is based on the hypothesis that MC-LR and ctHBx activate MAPK signaling to cause cancer by altering PP2A enzyme activity.…”
Section: Introductionmentioning
confidence: 99%
“…We performed a multivariate analysis, which showed that the PPP2CA gene may not be an independent risk factor for the poor prognosis of HCC. Gong et al 23 reported that PP2Ac expression plays a role in HCC tumorigenesis induced by HBV X protein, and PP2Ac protein overexpression is an independent predictor of poor OS of HCC patients. It can be seen that there are obvious differences between the two, which further proves the necessity of studying different subtypes of PP2Ac protein.…”
Section: Discussionmentioning
confidence: 99%